The Eve Decision — A Common Law Perspective - Keyserlingk, Edward (Revue générale de droit)

(untitled) (Éditions de l’Université d’Ottawa, 1987)
By its decision in the Eve case, the Supreme Court of Canada clarified and settled the law in at least two important respects. From now on, provincial statutes can only be used to authorize guardians to permit involuntary contraceptive sterilizations if their wording clearly and explicitly so provides. The Prince Edward Island statute in question did not do so. Secondly, though the Court's parens patriae jurisdiction is of unlimited scope and does extend to cases involving medical procedures, it cannot serve as the basis for authorizing non-therapeutic sterilizations. By ruling out the applicability of parens patriae, and by insisting that judges are not able to deal adequately with such cases, the Supreme Court may have strengthened the case for new legislation in this area. The writer argues that such legislation should provide for access to contraceptive sterilization for the mentally disabled, and the needed safeguards to protect those unable to consent or refuse from the imposition of sterilization in the interests of parties other than themselves.